2021
DOI: 10.3390/v13091832
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Subtypes and Natural Resistance Mutations in HCV Genotype 4 Infected Saudi Arabian Patients

Abstract: This study aimed to characterize the HCV genetic subtypes variability and the presence of natural occurring resistance-associated substitutions (RASs) in Saudi Arabia patients. A total of 17 GT patients were analyzed. Sequence analysis of NS3, NS5A, and NS5B regions was performed by direct sequencing, and phylogenetic analyses were used to determine genetic subtypes, RAS, and polymorphisms. Nine patients were infected by GT 4a, two with GT 4o and three with GT 4d. Two patients were infected with apparent recom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A meta‐analysis of HCV genotypes in 18 studies from Saudi Arabia also found that 52.6% of HCV infections were due to GT‐4 22 . Together, these studies confirmed the predominance and regional variability of HCV GT‐4 (60%–80%) in Saudi Arabia, but little data is available on the HCV‐4 subtype 23,24 . Furthermore, pangenotypic DAAs have some drawbacks, such as higher costs and the potential for the development of drug‐resistant strains of HCV.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A meta‐analysis of HCV genotypes in 18 studies from Saudi Arabia also found that 52.6% of HCV infections were due to GT‐4 22 . Together, these studies confirmed the predominance and regional variability of HCV GT‐4 (60%–80%) in Saudi Arabia, but little data is available on the HCV‐4 subtype 23,24 . Furthermore, pangenotypic DAAs have some drawbacks, such as higher costs and the potential for the development of drug‐resistant strains of HCV.…”
Section: Discussionmentioning
confidence: 92%
“…22 Together, these studies confirmed the predominance and regional variability of HCV GT-4 (60%-80%) in Saudi Arabia, but little data is available on the HCV-4 subtype. 23,24 Furthermore, pangenotypic DAAs have some drawbacks, such as higher costs and the potential for the development of drugresistant strains of HCV. Therefore, further studies on resistanceassociated variants (RAVs) are needed.…”
Section: Safety Of Treatment Received and Adverse Eventsmentioning
confidence: 99%
“…61 Genotype 4 subtypes, including 4d and 4o, have been identified in Saudi Arabia with a low prevalence. 64 Only subtype 5a and one yet unassigned subtype of genotype 5 are known. Subtype 5a is the most common genotype in South Africa, where the majority of cases are found (figure 2).…”
Section: Recent Advances In Clinical Practicementioning
confidence: 99%
“…Pattern one is characterized by high genetic diversity and involves the geographically discrete areas with different genotypes, such as in West Africa the most predominant types are 1, and 2, Central Africa with type 4, and Asia with types 3, and 6. According to a study based on the small genotypes 4 (GT 4) cohort, the most predominant genotype in Middle East region was observed as genotype 4 19 . However, HCV genotype 1 is the most prevalent among non-Arab countries in the region including Turkey, Iran, Cyprus, and Israel 20 .The genotype 6 is mainly distributed in southeast Asia and southern China 21 .…”
Section: Introductionmentioning
confidence: 99%